Followership behavior and leaders' trust: Do political skills matter? - Gulnaz Shahzadi; Albert John; Faisal Qadeer; Shamaila Mehnaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The study aims to examine the process and contingency to explain the relationship between follower's proactive behavior and leader's trust. Trust has been identified as one of the most critical elements of the high-quality relationship between a follower and leader and considered as a key boulevard through which followers can impact the behavior of their leaders. In this cross-sectional study, data is collected from leaders and followers (dyads) of a large corporation by conducting two self-administered surveys. Findings suggest that the proactive followers are more trustworthy in the eyes of their leaders. Perceived follower support plays a mediating role in this process. Further, we find that political skill of followers moderates this relationship. The study has significant implications for followership research, extending the comprehension about follower characteristics' effect on their behaviors and leaders perception. We contribute to followership literature by empirically validating the practices that help in trust building on followers providing a framework to practitioners for trust-building and empowering scholars for further identification of followers' behaviors and traits that can construct leaders' trust. The study indirectly expands the leadership literature and provides help to understand the leadership in the context of followership. These findings are useful for followers, leaders and for individuals who are involved in their development and training and invest and train employees for effective followership behavior. By improving the followership skills of employees advance the effective leadership outcome ultimately, therefore organizational improvement can be increased.
Keywords: 330; leaders' trust on followers; proactive behavior; followership behavior; perceived follower support; political skills